(3GdGNJjGQ aj TQM GdeNJGQ (B( (3aj aQhY GdMfajI (B)s - (3YHO Gddg Hf eMehO Hf ehOhO GdehUdjs; (3CHh GdaVd GdehUdj , eLO GdOjf CHh GdaVd YHO Gddg Hf eMehO Hf ehOhO GdehUdj GdHdOMj,J (B683 (3g` s
(3ChdgG (B:s
(3fGbUI ef ChdgG hChd GdehLhO efgG , jHOC HHGH GdJOHjQ s
(3BNQgG (B:s
(3SGFd ef eJTGHgg GdaQGFV gPG BNQ cJGH GdENJjGQ s
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3cJHJ YfGhjjf GdCHhGH hGdaUhd HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
Keywords: (3Gdabg GdMfajs